The effects of Ultraviolet-B radiation on Antarctic sea-ice algae1 - Ryan, KG; Andrew McMinn; Hegseth, EN; Davy, SK (2012)
The impacts of ultraviolet-B radiation (UVB) on polar sea-ice algal communities have not yet been demonstrated. We assess the impacts of UV on these communities using both laboratory experiments on algal isolates and by modification of the in situ spectral distribution of the under-ice irradiance. In the latter experiment, filters were attached to the upper surface of the ice so that the algae were exposed in situ to treatments of ambient levels of PAR and UV radiation, ambient radiation minus UVB, and ambient radiation minus all UV. After 16 d, significant increases in chl a and cell numbers were recorded for all treatments, but there were no significant differences among the different treatments. Bottom-ice algae exposed in vitro were considerably less tolerant to UVB than those in situ, but this tolerance improved when algae were retained within a solid block of ice. In addition, algae extracted from brine channels in the upper meter of sea ice and exposed to PAR and UVB in the laboratory were much more tolerant of high UVB doses than were any bottom-ice isolates. This finding indicates that brine algae may be better adapted to high PAR and UVB than are bottom-ice algae. The data indicate that the impact of increased levels of UVB resulting from springtime ozone depletion on Antarctic bottom-ice communities is likely to be minimal. These algae are likely protected by strong UVB attenuation by the overlying ice and snow, by other inorganic and organic substances in the ice matrix, and by algal cells closer to the surface.